2020
DOI: 10.1002/stem.3242
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell homing: From physiology to therapeutics

Abstract: Stem cell homing is a multistep endogenous physiologic process that is also used by exogenously administered hematopoietic stem and progenitor cells (HSPCs). This multistep process involves cell migration and is essential for hematopoietic stem cell transplantation. The process can be manipulated to enhance ultimate engraftment potential, and understanding stem cell homing is also important to the understanding of stem cell mobilization. Homing is also of potential importance in the recruitment of marrow mesen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
102
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(117 citation statements)
references
References 153 publications
(173 reference statements)
1
102
0
Order By: Relevance
“…In vivo studies have shown that such cell-cell interactions are essential for the migration, mobilization, and maintenance of HSPCs within BM 23 . Additionally, it is hypothesized that the first interaction during the homing of HSPC in BM is with the sinusoidal endothelium 34 . Therefore, our findings that HSPCs migrated more efficiently in BMOs containing a larger network-like structure, as well as the close proximity between the two cell types, suggest that our 3D system mimics essential parts of such cellular interactions found in natural BM 23,34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo studies have shown that such cell-cell interactions are essential for the migration, mobilization, and maintenance of HSPCs within BM 23 . Additionally, it is hypothesized that the first interaction during the homing of HSPC in BM is with the sinusoidal endothelium 34 . Therefore, our findings that HSPCs migrated more efficiently in BMOs containing a larger network-like structure, as well as the close proximity between the two cell types, suggest that our 3D system mimics essential parts of such cellular interactions found in natural BM 23,34 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is hypothesized that the first interaction during the homing of HSPC in BM is with the sinusoidal endothelium 34 . Therefore, our findings that HSPCs migrated more efficiently in BMOs containing a larger network-like structure, as well as the close proximity between the two cell types, suggest that our 3D system mimics essential parts of such cellular interactions found in natural BM 23,34 . Further investigation of the migration process of HSPCs in BMOs proposed a partial regulation of the CXCL12-CXCR4 signaling pathway, which is known to be the main regulator for human stem cell homing 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of sitagliptin, and other potential interventions that target BDMSC and decidual precursor cells [27], in mitigating the risk of adverse pregnancy outcome warrants further evaluation in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…CXCR4 and KIT) and trans-endothelial migration (e.g. ITGA4 and CD82) [27]. However, unlike IC, hPMC also express genes coding for secreted factors implicating in MSC self-renewal and engraftment ( Fig.…”
Section: Characterization Of Hpmc In Midluteal Endometriummentioning
confidence: 99%
“…A potential reason for the observed inconsistencies is the heterogeneity of cultured MSCs, which is influenced by the individual donor and tissue of origin, isolation technique, culture environment, and cell passage number (Wilson et al, 2019;Harman et al, 2020). Purposefully manipulating MSCs to improve therapeutic benefits, which by default could result in a more standardized and/or customized secretome, is not a novel idea, but one that has not yet been maximally explored (Liesveld et al, 2020;Ocansey et al, 2020).…”
Section: Manipulated Mscsmentioning
confidence: 99%